The Digitation Sign Facilitates Diagnosis of Shoulder Subscapularis Lesions on Preoperative Magnetic Resonance Imaging - Ana Nigues, M.D; Yves Salentiny, M.D; Marko Nabergoj, M.D; Alexandre Lädermann, M.D; Lionel Neyton, M.D (Elsevier, 2022)
Purpose: The purposes of this study were to investigate a radiographic sign found on coronal magnetic resonance imaging (MRI) sequences in subscapularis (SSC) pathology, reporting interobserver reliability data and sensitivity and specificity; and to correlate the preoperative assessment of SSC pathology with intraoperative assessment of the SSc during shoulder arthroscopy. Methods: A consecutive series of patients undergoing arthroscopic rotator cuff repair from January 2020 to December 2020 were examined. The positive diagnosis of a subscapularis tendon tear was prospectively determined and confirmed by arthroscopy. The "digitation sign" was assessed by 3 independent shoulder-trained fellows when evaluating the SSC in the coronal plane on T2-weighted images. Results: Of the 132 patients included, 74 (56%) had SSC tendon tears confirmed during arthroscopy. Interobserver agreement for digitation sign was substantial (k= 0.640). Sensitivity for digitation sign only was 74.3%; for criteria of Adams et al. (Accuracy of preoperative magnetic resonance imaging in predicting a subscapularis tendon tear based on arthroscopy; Arthroscopy 2010;26:1427-1433) only, 83.8%; and for the combination of the 2 methods, 89.2%. Specificity was 84.5% for digitation sign only, 77.6% for Adams et al. criteria only, and 67.2% for the combination of the 2 methods. Sensitivity is statistically better when the digitation sign is added to the Adams et al. criteria for detection of SSC lesions. As expected, specificity is statistically lower. SSC tears are significantly associated with biceps lesions. Conclusion: Preoperative systematic MRI evaluation by shoulder surgeons can diagnose subscapularis lesions by using the digitation sign in the coronal plane along with Adams et al. criteria, leading to good sensitivity. This easy-to-apply sign can be helpful in the initial MRI evaluation in the coronal plane, with improved sensitivity when combined with a systematic approach. Level of Evidence: II, study of diagnostic test.